Flow Experiences and Willingness to Communicate: Connecting Scottish Gaelic Language and Traditional Music. (September 2019) - MacIntyre, Peter D.; Ross, Jessica; Sparling, Heather
This brief report examines correlations between intense, highly motivating flow experiences, perceptions of competence, and willingness to communicate in both language and music, in the context of Scottish Gaelic and traditional music. The sample of 54 persons, mostly from Canada and Scotland, was contacted via Facebook groups. The frequency of flow experiences correlated highly between language and music contexts. Correlations for willingness to communicate/play and perceived competence with language and music also are reported. Results are interpreted as reflecting a combination of social (e.g., identity) and personality-based (e.g., autotelic) processes.